Prenatal sonographic diagnosis of cloacal malformation associated with uterus didelphys and bilateral hydrometrocolpos: a case report - Xing Xu; Hongxia Yuan; Rong Tian; Xiaohong Lu; Lingling Li (BMC Pregnancy and Childbirth)
Abstract Introduction Cloacal malformation is a rare and complex group of congenital abnormalities involving anomalies of the genitourinary and gastrointestinal systems. The most common prenatal ultrasound finding is the presence of abnormal pelvic cystic masses. Case presentation We present a case of cloacal malformation associated with uterus didelphys and bilateral hydrometrocolpos, diagnosed by prenatal ultrasound at 29 weeks of gestation. The diagnosis was confirmed by postmortem examination following induced labor. Conclusion Abnormal pelvic cystic masses detected prenatally require close observation and monitoring. Prenatal ultrasound provides accurate and detailed diagnostic information, which is crucial to prenatal counseling and management.